Estimulación sensorial y su influencia en el proceso de enseñanza- aprendizaje en estudiantes de educación inicial - Játiva Martinez, Mack Bryan (2024)
This thesis investigates how sensory stimulation influences the teaching-learning process in children in Initial Education II at the Adolfo María Astudillo Educational Unit in the Babahoyo canton, Los Ríos Province. Sensory stimuli promote the comprehensive development and learning of children through experiences and activities that involve the senses. Through a documentary and field approach, the research problem is examined using bibliographies and surveys. The central issue addressed by this research is how sensory stimulation influences the teaching-learning process in early education students. This thesis focuses on the benefits of sensory stimulation and how it helps improve a child's concentration and coordination. The general objective is to establish the role of sensory stimulation and its influence on the teaching-learning process in early education students. The results obtained indicate and demonstrate that the observation form showed a lack of sensory stimulation in the language aspect, and additional strategic activities are needed to achieve improvement in speech. It was also observed that only a few students require increased sensory activities. Additionally, it was observed how children could perform each of the activities, interacting by asking questions and discovering new things with their minds through the use of their senses.